Environmental Tax Reform : Principles from Theory and Practice to Date - Parry, Ian (IMF Working Papers; Working Paper ;, 2012)
This paper recommends a system of upstream taxes on fossil fuels, combined with refunds for downstream emissions capture, to reduce carbon and local pollution emissions. Motor fuel taxes should also account for congestion and other externalities associated with vehicle use, at least until mileage-based taxes are widely introduced. An examination of existing energy/environmental tax systems in Germany, Sweden, Turkey, and Vietnam suggests that there is substantial scope for policy reform. This includes harmonizing taxes for pollution content across different fuels and end-users, better aligning tax rates with values for externalities, and scaling back taxes on vehicle ownership and electricity use that are redundant (on environmental grounds) in the presence of more targeted taxes.